Analysis of Reading Ability, Drafting Skills and Students' Complaints on Engineering Drawing of Grade XI of Machining Study Program - Yondi Akhiruddin; Subiyono Subiyono (Department of Mechanical Engineering Education, 2017)
This study aims to determine and describe students' reading ability and drafting skills on technical drawing, and the students' complaints of school factors, which affect the learning process on engineering drawing subject in grade XI of Machining study program. This is a descriptive research with a quantitative approach. The population in this research were 112 students. The samples of 91 students were chosen using simple random sampling technique. Data were collected by means of tests and questionnaire. Data were then analyzed using descriptive analysis. The result shows that students' reading ability of engineering drawing is in the category of